Hands-on Linux administration on Azure : develop, maintain, and automate applications on the Azure cloud platform /: develop, maintain, and automate applications on the Azure cloud platform. (2020) - Ganesan, Kamesh; Skaria, Rithin; Vos, Frederik
No abstract available